Techniques to improve the limited degree of freedom inherent from laparoscopic surgery during laparoscopic duct-to-mucosa pancreaticojejunostomy. (August 2022) - Lee, Boram; Yoon, Yoo-Seok; Han, Ho-Seong; Lee, Jun Suh
Highlights: Laparoscopic pancreaticojejunostomy (PJ) is a technical demanding procedure. We describe our technique for overcoming technical difficulties of laparoscopic PJ. Main trocars should be placed perpendicular to the anastomosis line. Alternative use of multiple trocars is useful to encompass the 360-degree anastomosis.